The grain size effect on pores structure characteristics of high-rank coal before and after the methane adsorption - Teng Li (Journal of Natural Gas Geoscience, 2021)
Methane adsorption characteristics and pore structure are two essential parameters to evaluate the reservoir quality of coal. However, as a result of the frequent increased and decreased pressure on the coal during the methane adsorption, the pore structure of the coal can be altered. The high-rank coal was obtained from western Guizhou, China, and ground into three separate particle sizes, with methane adsorption measurements performed on these sub-samples. In addition, the dynamic change of the pore structure was calculated using low-temperature nitrogen adsorption and low-temperature carbon dioxide adsorption before and after the methane adsorption. The analysis indicate that the isothermal adsorption curves of the various grain sizes coal samples present no significant differences, while the adsorption rate and maximum excess adsorption capacity increase as particle sizes decrease. Until methane adsorption, the d(qde−qad)′ decreases as grain sizes decrease, while the d(qde−qad)′ decreases first and then increases for equal adsorption rate. Then, the d(qde−qad)′ for DY-5 coal sample decreases after methane adsorption, while it increases for the DY-6 and DY-7 coal samples, suggesting that the methane adsorption has a major impact on the meso- and macropore structure for the small grain sizes coal samples. Finally, at any time during the methane adsorption process, the pore structures in the coal might change. Pore connectivity is improved in coal samples with larger sizes, while after methane adsorption, the distribution of pores is more concentrated in coal samples with smaller grain sizes.